Feed contaminated by fumonisin (Fusarium spp.) in chicks has a negative influence on oxidative stress and performance, and the inclusion of curcumin-loaded nanocapsules minimizes these effects - Galli G.M. (2020)
© 2020 Elsevier LtdThe aim of this study was to determine whether the addition of curcumin (free and encapsulated) to chick feed would minimize the negative effects on health and performance caused by daily intake of fumonisin. We used 50 birds, divided into five treatments: CP, basal diet with 600 mg/kg of fumonisin, with antibiotic and coccidiostatic agent; CU, 600 mg/kg of fumonisin and 50 mg/kg of curcumin; NC5, feed with 600 mg/kg of fumonisin and 5 mg of nano-curcumin/kg of feed; NC10, feed with 600 mg/kg of fumonisin and 10 mg of nano-curcumin/kg of feed; and CN, fumonisin-free diet, with antibiotic and coccidiostatic. We measured weights, weight gain, and serum biochemistry, as well as antioxidant and oxidant activities. Lower body weight and weight gain were observed in chicks that received feed with fumonisin; curcumin did not minimize this negative effect. Lower glucose and triglyceride levels were also observed in the NC10 group, while the highest cholesterol levels were observed in all groups of birds that consumed fumonisin compared to the CN group. Uric acid levels were significantly lower in CP than in CN. Levels of liver enzymes were higher in CP than in CN. The highest levels of thiobarbituric acid reactive substances were found in CP and CU, whereas ROS was higher in CU compared to CN. Superoxide dismutase activity was significantly lower in CP, while glutathione S-transferase activity was higher in the CP group. Catalase activity was lower in groups of birds that consumed fumonisin compared to CN. Taken together, these findings suggest that intake of curcumin-loaded nanocapsules (10 mg/kg) had hepaprotective and antioxidant effects in chicks artificially intoxicated with fumonisin, minimizing the negative effects caused by this mycotoxin.